(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
The program of physical education of schoolchildren provides for various forms of organizing classes aimed at compensating for the lack of physical activity that occurs in the conditions of an intensive general education process. The purpose of the study is to develop and test the effectiveness of methods and means of forming a positive attitude of high school students to physical education. Participants: The participants are 11th grade students in the amount of 26 people (14 girls, 12 boys) of the Municipal Institution “Kharkiv Lyceum № 169 of the Kharkiv City”. The experiment lasted 9 weeks from March to May 2024. At the beginning and end of the experiment, an interactive survey was conducted using a Google form. Research methods: theoretical analysis and synthesis of scientific literature, questionnaire method, methods of mathematical statistics: the results of the questionnaire were compared using the connectivity tables. Results: an experimental program combining regular physical education lessons with various activities was implemented to interest and engage schoolchildren in physical activity. One of the 3 physical education lessons of the study group was devoted to an event, namely the “10 thousand steps” challenge, the “TikTok Sport Challenge”, lectures on healthy lifestyles and Olympic Ukraine, an online press conference with prominent athletes, online conferences “My favorite sport”, and “Self-government Day”. It was found that the results of positive answers to the questionnaire have a significantly higher rate after the experiment (p<0.05; p<0.01). Conclusions: The effectiveness of using a set of online and offline activities has been shown, which contributed to increasing students’ interest in classes, developing their motivation for physical activity, expanding knowledge about a healthy lifestyle, forming a positive emotional attitude to sports, as well as improving physical fitness and social skills.